If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -5x = -2(x + -3) Reorder the terms: 12 + -5x = -2(-3 + x) 12 + -5x = (-3 * -2 + x * -2) 12 + -5x = (6 + -2x) Solving 12 + -5x = 6 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 12 + -5x + 2x = 6 + -2x + 2x Combine like terms: -5x + 2x = -3x 12 + -3x = 6 + -2x + 2x Combine like terms: -2x + 2x = 0 12 + -3x = 6 + 0 12 + -3x = 6 Add '-12' to each side of the equation. 12 + -12 + -3x = 6 + -12 Combine like terms: 12 + -12 = 0 0 + -3x = 6 + -12 -3x = 6 + -12 Combine like terms: 6 + -12 = -6 -3x = -6 Divide each side by '-3'. x = 2 Simplifying x = 2
| 3p+16=2p+7 | | 14=6(5y-3) | | -11+x=37 | | -5x^6-10x^5+40x^4= | | f(x)=30cos(6x^4) | | -2x^2+8x+64=0 | | 4y=3-2 | | Y=15x-10 | | -5x^2-9x-8=0 | | 3x-3y=33 | | 2-3(x+4)=18 | | (3x+1)+49=180 | | y=-2.50x+b | | 8x+5=-40 | | (-0)-2y=6 | | 9(g+-1)=-12 | | 4-3(2x+6)=6-5(x+2) | | 9(g+-1)=-26 | | -x-2(0)=6 | | x-7.1=2.5 | | 5(-10-4x)=-240 | | m-4.6=1.4 | | -4v+15=-26 | | y=-.5(0)-3 | | 1-6x=-4x-1 | | 50=2n+22 | | -4v+15=26 | | -7x-5y=3 | | 36+3x=180 | | 6g-4+3g+2=2g | | 6a^8+10a^3-3a^4= | | 6(2)+y=12 |